Coherent risk measures and arbitrage - Cullender, Stuart F. (My University, 2013)
No abstract provided
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, in fulfillment of the requirements for the degree of Master of Science, April 2013.
Keywords: Risk management.; Arbitrage.